THREE PHASE UNDERGROUND CABLE DETECTION USING ARDUINO - Tanaya Mahendra Gurav 1, Sanjivani Hanmant Navale 1, Trupti Vikas Pawar 1, Pragati Vasant Rathod 1, Y.R.Nagtilak 2 (International Journal of Innovations in Engineering Research and Technology, 2022)
The underground cable system is a common practice followed in many urban areas. While a fault occurs for some reason, at that time the repairing process related to that particular cable is difficult due to not knowing the exact location of the cable fault. The proposed system is to find the exact location of the fault. The objective of this work is to determine the distance of underground cable fault from base station in kilometers using an Arduino. In this proposed work, when a low DC voltage is applied at the feeder end through a series resistor (cable lines), then current would vary depending upon the location of fault in the cable. In case there is a short circuit, the voltage across series resistors changes accordingly, this is then fed to inbuilt ADC of Arduino to develop precise digital data for display in kilometers. The project is assembled with a set of resistors representing the cable length in km and the fault creation is made by a set of switches at every known km to cross check the accuracy of the same. The fault occurring at a particular distance, the respective phase along with the distance is displayed on the LCD.